2009
DOI: 10.1016/j.exphem.2009.05.005
|View full text |Cite
|
Sign up to set email alerts
|

In vivo inactivation of MASTL kinase results in thrombocytopenia

Abstract: Objective-A missense mutation in the Microtubule Associated Serine/Threonine Like kinase gene (MASTL, FLJ14813) on human chromosome 10 was previously linked to a novel form of autosomal dominant inherited thrombocytopenia in a single pedigree. The mutation results in an amino acid change from glutamic acid at position 167 to aspartic acid and segregates perfectly with thrombocytopenic individuals within this extended family. The phenotype is characterized by mild thrombocytopenia with an average platelet count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…19 A functional genomic screen found MASTL as a potential determinant of taxol sensitivity and showed that depletion of MASTL induces polyploidy in the colon cancer cell line HCT-116. 21 Furthermore, MASTL may help to prevent thrombocytopenia (a low thrombocyte count) 22,23 and is suggested to control endocytic transport. 24 However, no function for MASTL in the cell cycle had been described.…”
Section: Resultsmentioning
confidence: 99%
“…19 A functional genomic screen found MASTL as a potential determinant of taxol sensitivity and showed that depletion of MASTL induces polyploidy in the colon cancer cell line HCT-116. 21 Furthermore, MASTL may help to prevent thrombocytopenia (a low thrombocyte count) 22,23 and is suggested to control endocytic transport. 24 However, no function for MASTL in the cell cycle had been described.…”
Section: Resultsmentioning
confidence: 99%
“…Both of these publications focus on the role of MAST-L in autosomal-dominant thrombocytopenia, showing that a single-point mutation (E167D) in the N-terminal kinase domain correlates with this syndrome (12), and transient knockdown in zebrafish results in a reduction of circulating thrombocytes (13).…”
mentioning
confidence: 99%
“…After localization of a locus on human chromosome 10p, the microtubule-associated serine/threonine-like kinase (MASTL) gene was identified as a candidate. Knockdown of the zebrafish ortholog with MOs resulted in reduction of circulating thrombocytes, as well as decreased expression of itga2b and mpl , providing supportive evidence [50]. MO knockdown in zebrafish also reinforced the discoveries of NBEAL2 and RBM8A as the affected genes in the gray platelet and thrombocytopenia with absent radii syndromes, respectively [51,52].…”
Section: Dissection Of Human Coagulation and Associated Disorders Usimentioning
confidence: 81%